2018
DOI: 10.1292/jvms.18-0306
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of WBN/Kob diabetic fatty rats supplemented with a fructose-rich diet as a metabolic syndrome model: response to a GLP-1 receptor agonist

Abstract: The incidence of metabolic syndrome is rapidly increasing worldwide, and adequate animal models are crucial for studies on its pathogenesis and therapy. In the search of an adequate experimental model to simulate human metabolic syndrome, the present study was performed to examine the pharmacological response of WBN/Kob-Leprfa (WBKDF) rats supplemented with a fructose-rich diet (FRD) to liraglutide, a GLP-1 receptor agonist. Male WBKDF rats fed FRD at 7 weeks of age were divided into 3 groups, and administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Similarly, in the present study, we found a significant reduction in plasma glucose levels and glucose tolerance aggravated by HFD supplementation in WBKDF rats. These anti‐hyperglycemic effects of liraglutide were probably due to its insulinotropic action …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, in the present study, we found a significant reduction in plasma glucose levels and glucose tolerance aggravated by HFD supplementation in WBKDF rats. These anti‐hyperglycemic effects of liraglutide were probably due to its insulinotropic action …”
Section: Discussionsupporting
confidence: 92%
“…They received subcutaneous injections of either saline or liraglutide (Victoza; Novo Nordisk Pharma) at doses of 75 or 300 μg/kg body weight once daily for 4 weeks. The doses of liraglutide were determined according to results from previous studies . Blood samples were taken once weekly from the tail vein of nonfasting and conscious rats and plasma was used for glucose measurement.…”
Section: Methodsmentioning
confidence: 99%
“…WBN/Kob diabetic fatty rats represent a congenic strain carrying the fa allele of the leptin receptor gene (Lepr) that exhibits obesity, insulin resistance, and diabetes (62,63). WBN/Kob diabetic fatty rats fed a high-fructose diet for 4 weeks showed significant diffuse fatty degeneration (64). In addition, WBN/Kob diabetic fatty rats fed a high-fat diet for 4 weeks showed diffuse fatty changes with hepatocellular hypertrophy (65).…”
Section: Genetic Nafld/nash Rat Modelsmentioning
confidence: 99%